(untitled) (Revista de Investigaciones Universidad del Quindío, 2022)
The paper attempts to analyze the role and importance of law in the development of the digital economy, as well as enforcement and incentive measures. This is a descriptive study, and an overview of the most important normative acts regulating the development of the digital economy in Russia is given. Various aspects of the reverse impact of the digital economy on the law itself are considered. The conclusion is made that many risks and dangers are exaggerated, but there are also real threats to the harmonious development of society, including technocratism, mechanisticism, transhumanism, the destruction of traditional values, the transformation of justice into an algorithm, and information extremism.